STRATEGI PENGELOLAAN ZIS PADA MUSIM PANDEMI COVID-19 (STUDI PADA BAZNAS SIDOARJO) - Sri Hariyanti; Suhaela Rahmawati (Faculty of Islamic Economic and Business (FEBI), Sayyid Ali Rahmatullah State Islamic University (UIN SATU) Tulungagung, 2022)
ZIS stands for Zakat, Infaq, and Shadaqah, for its management is officially carried out by BAZNAS or the National Amil Zakat Agency because this institution is the official and only body established by the government based on Presidential Decree No. 8 of 2001 which has the task and function of collecting and distributing zakat, infaq, and alms (ZIS) at the national level. However, at the beginning of 2020 ZIS management activities underwent a slight change due to the Covid-19 pandemic which caused social activities to be limited and the economic decline in Indonesia. Because of this in this article, we will focus on discussing how to manage ZIS strategies during the COVID-19 pandemic study season. at BAZNAS Sidoarjo. The research method used is descriptive qualitative, namely the research method used to investigate, find, describe and explain the quality or features of social influences that cannot be described, measured or described through a quantitative approach. The results of this study include making it easier for people to pay zakat/infaq and shadaqah at BAZNAS Sidoarjo using barcodes that can be paid through online payment applications such as gopay, ovo, link aja, funds, or other merchants/banks. As for the distribution, BAZNAS gave an invitation to Mustahiq to come to the BAZNAS office in stages, so as not to cause crowds and required to always implement health protocols.